Diphenyl diselenide supplementation in infected mice by Toxoplasma gondii: Protective effect on behavior, neuromodulation and oxidative stress caused by disease - Machado V.S. (2016)
© 2016 Elsevier Inc.The aim of this study was to evaluate the effect of subcutaneous administration of diphenyl diselenide (PhSe)2 on animal behavior and activities of acetylcholinesterase (AChE), adenylate kinase (AK), and creatine kinase (CK) in the brain of mice infected by Toxoplasma gondii. In addition, thiobarbituric acid reactive species (TBARS) levels and glutathione (GR, GPx and GST) activity were also evaluated. For the study, 40 female mice were divided into four groups of 10 animals each: group A (uninfected and untreated), group B (uninfected and treated with (PhSe)2), group C (infected and untreated) and group D (infected and treated with (PhSe)2). The mice were inoculated with 50 cysts of the ME49 strain of T. gondii. After infection the animals of the groups B and D were treated on days 1 and 20 post-infection (PI) with 5.0 μmol/kg of (PhSe)2 subcutaneously. Behavioral tests were conducted on days 29 PI to assess memory loss (object recognition), anxiety (elevated plus maze), locomotor and exploratory activity (Open Field) and it was found out that infected and untreated animals (group C) had developed anxiety and memory impairment, and the (PhSe)2 treatment did not reverse these behavioral changes on infected animals treated with (PhSe)2 (group D). The results showed an increase on AChE activity (P < 0.01) in the brain of infected and untreated animals (group C) compared to the uninfected and untreated animals (group A). The AK and CK activities decreased in infected and untreated animals (group C) compared to the uninfected and untreated animals (group A) (P < 0.01), however the (PhSe)2 treatment did not reverse these alterations. Infected and untreated animals (group C) showed increased TBARS levels and GR activity, and decreased GPx and GST activities when compared to uninfected and untreated animals (group A). Infected animals treated with (PhSe)2 (group D) decreased TBARS levels and GR activity, while increased GST activity when compared to infected and untreated animals (group C). It was concluded that (PhSe)2 showed antioxidant activity, but the dose used had no anti-inflammatory effect and failed to reverse the behavioral changes caused by the parasite.